Analysis of Language Style in the Syair Dagang by Hamzah Fansuri - R. Myrna Nur Sakinah; Nurhayati, Cucu (Islah: Journal of Islamic Literature and History, 2025)
This study aims to examine the use of figurative language in Syair Dagang by Hamzah Fansuri. Hamzah Fansuri is recognized as one of the prominent literary figures during the golden age of Islamic kingdoms in the Indonesian Archipelago, particularly in 16th century Aceh. The research employs a qualitative method with a descriptive approach. Data were collected through online sources and analyzed using reading and note-taking techniques. The analysis reveals several types of figurative language found in the poem. Four types of figures of speech were identified: metaphor (2 instances), antithesis (1 instance), simile (1 instance), and repetition (5 instances). In addition, 19 significant diction choices were found that enrich the overall meaning of the poem. These findings indicate that Hamzah Fansuri’s use of stylistic elements and diction not only enhances the aesthetic quality of the poem but also deepens its spiritual and philosophical messages.